Heart Transplantation Survival and the Use of Traumatically Brain‐Injured Donors: UNOS Registry Propensity‐Matched Analysis. Issue 17 (3rd September 2019) - Barac, Yaron D.; Jawitz, Oliver K.; Klapper, Jacob; Schroder, Jacob; Daneshmand, Mani A.; Patel, Chet; Hartwig, Matt G.; Sweitzer, Nancy K.; Milano, Carmelo A.
Abstract : Background: The transplantation of hearts from traumatically brain‐injured (TBI) donors has been associated with inferior long‐term survival in single‐center analyses. However, in a more recent analysis, death caused by cerebrovascular accident was associated with worse posttransplant survival in recipients. The purpose of this study was to explore the outcomes of heart transplantation in recipients receiving donor hearts from TBI and non‐TBI donors in a large national registry. Methods and Results: We performed a retrospective cohort analysis of the UNOS (United Network of Organ Sharing) Registry Organ Procurement and Transplantation Network between 2006 and 2018 for adult candidates wait‐listed for isolated heart transplantation. Recipients were stratified into 2 groups, TBI and non‐TBI donors. Propensity score matching was performed. Kaplan‐Meier analysis was used to estimate survival posttransplant. A total of 24 894 candidates met inclusion criteria. TBI was the leading cause of death in the donor population. Recipients of TBI donor hearts (N=13 07) were younger (median age, 55 versus 57 years; P <0.001) and less likely women (21.6% versus 29.8%; P <0.001). At 10 years, the TBI group had better long‐term survival compared with the non‐TBI group (62.8% versus 59.9%; P <0.001). After propensity group matching, the 10‐year survival was similar between groups. Conclusions: In the largest analysis of heart transplants and their survival, according to the type of donor injury (TBI versus non‐TBI), we found similar survival in heart transplant recipients. Future studies should address specific subpopulations (eg, hemorrhagic stroke) in the non‐TBI group to address concerns about reduced posttransplant survival.